62.7k views
0 votes
Which shows this equation in standard form? 6 – 2(x – y) = 3x + 5

A) 5x – 2y = 1

B) 5x – 2y = –1

C) 5x + 2y = 1

D) 2x – 5y = 1

User AmooAti
by
5.3k points

2 Answers

3 votes

Answer: B


Step-by-step explanation: 6-2(x-y)=3x+5

6-2x+2y=3x+5

6+2y=5x+5

1+2y=5x

1=5x-2y

or

5x-2y=1


User Alex Derkach
by
5.0k points
7 votes

standard formis Ax +By = C


6 -2(x-y) = 3x+5

6 -2x+2y = 3x+5

subtract 3x from each side

6 -5x +2y = 5

subtract 6 from each side

-5x +2y = -1

divide each side by -1

5x -2y = 1

A

User Wes Ruvalcaba
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.